PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE MELALUI CUSTOMER SATISFACTION DAN SERVICE QUALITY PADA PERUSAHAAN ASURANSI JIWA DI SURABAYA - Veronica Lavenia Irawan; Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of Leadership Style to Service Quality, Leadership Style to Financial Performance, Service Quality to Financial Performance, Service Quality to Customer’s Satisfaction and Customer’s Satisfaction to Financial Performance on life insurance firms in Surabaya. The samples used in this study was 30 life insurance firms in Surabaya listed on Book Directories of Insurance Otoritas Jasa Keuangan 2014, with each of 10 employees and 10 customers in each firm. The data analysis technique used in this research was SmartPLS software.This study showed that there was positive and significant relationship of Leadership Style to Service Quality, Leadership Style to Financial Performance, Service Quality to Financial Performance, Service Quality to Customer’s Satisfaction and Customer’s Satisfaction to Financial Performance on life insurance firms in Surabaya.